Carbon finance in Malaysia: an analysis of issues and challenges - Sifat, Imtiaz; Mohd Thas Thaker, Hassanudin; Karim, Ridoan (Palgrave McMillan, 2024)
Trading greenhouse gas emissions is gaining importance as a means to combat the hazards of climate change. In her pursuit of a lower carbon footprint in the economy, Malaysia, a middle-income country, has undertaken a multi-pronged approach of schemes and actions. Key among them is the Clean Development Scheme (CDM), which has been operational for a significant number of years now. This paper's main thrusts are the analyses and appraisal of the performance of the CDM scheme. We further review the existing challenges and opportunities to improve low-carbon pursuit of Malaysia. Our review finds that the existing legislation, policies, and implementation of market mechanisms are inadequate in achieving the targets Malaysia set for herself. Moreover, greater stakeholder engagement and spreading of awareness are needed in order for Malaysia to enjoy the fruits of its current actions.